KAJIAN KALIMAT YANG MENGANDUNG KONSEP BUSHIDO OLEH TOKOH KINEMON DALAM ANIME ONE PIECE KARYA EICHIRO ODA (SEBUAH TINJAUAN SOSIOLINGUISTIK - Muhammad Hasanuddin; Sri Wahyu Widiati; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to describe the relationship of ethic code of bushido concept on words, phrases, and sentences spoken by figure Kinemon and to determine the form of sociolinguistic analysisof the relationship between language and culture in sentence uttered by figure Kinemon on ethics codein concept“bushido”. In this study, the writer used a qualitative analysis research method. The object of this research was“One Piece” anime episod 581th chapter Punk hazard that became the early occurrence Kinemon figures. Data collection techniques in this study was“see and note” that focused on sentence of uttered by prominent Kinemon with eight reference of ethics code method became a basic of a samurai. The results of this study are expected to enrich the knowledge of the cultural discourse of bushido and to provide an understanding of the application ofbushido ethics code on speech acts shown by Kinemon.Key Words: Bushido, Ethics Code, Kinemon One Piece, Sociolinguistics.